Konfrontasi Iran-Amerika Serikat di Selat Hormuz dan Dampaknya bagi Distribusi Penjualan Minyak Dunia - Hasibuan, Wandy Ardiyansyah (Jurnal ICMES, 2020)
This paper will discuss why the confrontation between Iran and the United States (US) in the Strait of Hormuz occurred. After withdrawing from the Joint Comprehensive Plan of Action (JCPOA) agreement, US unilaterally giving back their sanctions to Iran and made relations between the two countries heated up again. Iran then responded with snarling to close the Strait of Hormuz. This response makes other countries in the world who have an interest in buying oil from the Middle East under threat. The US felt aggrieved by this threat; the country performs maneuvers and military confrontation in the Strait of Hormuz. This action caused oil traffic through the strait disturbed, and global oil distribution also harmed. By using qualitative methods and implementing Lovell's theory of Foreign Policy Strategy, the author finds that Iran and US use the Confrontation Strategy approach in its foreign policy, which prioritized contradictory national interests. As a result, it is predicted that the confrontation in the Strait of Hormuz will continue as long as the two sides hold their current positions.